To accelerate cancer prevention in Europe: Challenges for cancer registries. (November 2018) - Zanetti, R.; Sacchetto, L.; Coebergh, J.W.; Rosso, S.
Abstract: The availability of population-based cancer registry (CR) data is paramount in the development of modern oncology. Major contributions consisted in accurately measuring cancer burden (incidence, survival and prevalence, beside mortality), identifying and quantifying risk factors (case control and cohort studies that, in the last two decades, included gene variant assessment) and evaluating outcomes of treatments and preventive interventions, including mass screening. Cancer registration coverage of European populations progressed slowly since 1940 and is now almost 50%. Areas lacking high-quality national population-based cancer registration still exist within large countries such as France, Italy, Romania and Spain, Germany and Poland having national plans and legislation to reach complete coverage. Depending on programme ownership, history and institutional organisation, European CRs showed huge variations in the scope (research domain), size, available resources and finally exploitation of collected data. This reflects their heterogeneous origins stemming from different professional backgrounds and healthcare systems. This review discusses not only the potential for contributing to acceleration of prevention but also the coverage expansion by and innovation of CR organizations. The latter can be attained not only by more standardisation in institutional organisation and operative methodologies but also by intensification of scientific production and risk communication. The CR's agenda should focus on cancers caused by identifiable risk factor(s) that are amenable to preventive actions, including early detection; short-term priorities usually are with tobacco, and medium-term priorities are with alcohol, occupational exposures, infection-related cancers and ultraviolet-related skin cancers, while obesity-related cancers are likely to increase gradually further in the long term.